2018
DOI: 10.1007/s00405-018-4889-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the second version of the LittlEARS® Early Speech Production Questionnaire (LEESPQ) in German-speaking children with normal hearing

Abstract: The second version of the LEESPQ is a valid instrument for assessing early speech production of children aged 0‒18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
2
3
0
1
Order By: Relevance
“…This has been demonstrated by the significant Pearson correlation between the age of children and the parents' responses to the questionnaire. Similar results have been reported in other related studies [4][5][6] indicating that older children have improved speech production abilities as measured by LEESPQ. On the other hand, there was no influence of gender (p=0.12) or bilingualism (p=0.28) on the early speech production in the Arabic-speaking children as reported in the studies of validating the Turkish and German versions of LEESPQ.…”
Section: Statistical Analysis the Correlation Between The Positive Response (Yes) Probability And Age Has Been Tested Using Pearson Corresupporting
confidence: 91%
See 3 more Smart Citations
“…This has been demonstrated by the significant Pearson correlation between the age of children and the parents' responses to the questionnaire. Similar results have been reported in other related studies [4][5][6] indicating that older children have improved speech production abilities as measured by LEESPQ. On the other hand, there was no influence of gender (p=0.12) or bilingualism (p=0.28) on the early speech production in the Arabic-speaking children as reported in the studies of validating the Turkish and German versions of LEESPQ.…”
Section: Statistical Analysis the Correlation Between The Positive Response (Yes) Probability And Age Has Been Tested Using Pearson Corresupporting
confidence: 91%
“…These results were in accordance with the results of similar studies of validating LEESPQ for other languages. [4][5][6] Moreover, the results of the current study confirmed that Arabic-LEESPQ scores are significantly correlated with age. This has been demonstrated by the significant Pearson correlation between the age of children and the parents' responses to the questionnaire.…”
Section: Statistical Analysis the Correlation Between The Positive Response (Yes) Probability And Age Has Been Tested Using Pearson Corresupporting
confidence: 81%
See 2 more Smart Citations
“…: identyfikację, dyskryminację czy lokalizację źródła dźwięku. Wyniki ankiety pozwalają na wyznaczenie aktualnego wieku słuchowego dziecka oraz opóźnienia rozwoju słuchowego względem dzieci słyszących prawidłowo [10][11][12][13]. Przeprowadzenie badania behawioralnej audiometrii obserwacyjnej oraz wypełnienie kwestionariusza pozwala na wiarygodną ocenę skuteczności zastosowanych protez słuchowych [14].…”
Section: Wstępunclassified